(untitled) (Conferencea, 2023)
Currently, in order to provide the population with natural silk fabrics, various scientific studies are being conducted aimed at creating and introducing into the sericulture of Uzbekistan breeds and hybrids of silkworm with high combinational value, with maximum manifestation of heterosis, with low cost of raw silk. However, not enough has been done in the direction of creating 100% pure, highly heterotic silkworm hybrids, and therefore it is necessary to conduct in-depth scientific research. In this regard, the research of this work makes it possible to solve the problem common to all sericulture countries of the world of creating 100% pure hybrids by using sex-labeled breeds at the greening stage.